Consequences of employment self-etching primer adhesive in orthodontic practice - Ali R Al-Khatib (University of Mosul, College of Dentistry, 2004)
The purposes of this study were to evaluate the shear bonding strength of stainless steel brackets bonded with self-etching primer adhesive system (Trans-bondTM 3M Uniteck, Monrovia, California, USA), compared with same system which employ 35% phosphoric acid gel, separated primer and adhesive. Also to assess and compare clinically the brackets bonding failure rate after using the 2 different techniques in orthodontic patients and to examine bracket / adhesive failure mode by using modified adhesive remnant index (MARI). Fifty six extracted human premolars used in the laboratory part, they were divided into 2 groups (I and II), each one subdivided into upper first and second, lower first and second premolars; 7 for each subgroup. In the first group bonding was carried out by using the conventional technique (phosphoric acid / adhesive) while in the second one, the self-etching primer was used. In the clinical part 15 patients with upper and lower fixed appliances (central, lateral incisors, canines and premolars) with 13-16 years old. The fol-low up period extended into 12-15 months. The statistical analyses in the laboratory (in vitro) part reported significantly lower but acceptable shear bond strength (8.69 and 8.42 MPa) for the upper first and second premolars, and 8.13 and 8.99 MPa for lower first and second premolars in comparison with the conventional groups (11.61 and 11.63 MPa) for upper first and second premolars, and 11.48 and 11.59 MPa for the lower first and second premolars as t-values were significant (2.69, 3.05 for the upper first and second premolars; 2.68, 2.45 for the lower first and second premolars) at p < 0.05 between study groups, but in the clinical trial no significant difference between the groups were recorded in relation to bonding failure rate as values of Z test of two proportions were ranged between 0.98 and 1.94, 0.00 and 1.94 for the upper and lower arches respectively, in spite of the higher percentages of failure rate for the self-etching primer adhesive group. The MARI reported higher frequencies at score 2, and score 3 for the control and experimental (self-etching primer) groups respectively. It can be concluded that in spite of the lower bonding strength values for the self- etching primer adhesive, but the results appear to be acceptable and this adhesive is recommended to be used in orthodontic practice. In accompanied to that the residual adhesive amount were smaller than those of the conventional one so that less damage happened to enamel surface during debonding procedures.